Influence of flowable materials on microleakage of nanofilled and hybrid Class II composite restorations with LED and QTH LCUs - Sadeghi Mostafa (Indian Journal of Dental Research, 2009)
Background: Class II composite restorations are more frequently being placed with margins apical to the cementoenamel junction (CEJ) and margins within the dentin are prone to microleakage. Aims: This in vitro study was used to evaluate the influence of flowable composite and flowable compomer as gingival liner on microleakage in Class II composite restorations and compare a light-emitting diode (LED) unit with a quartz tungsten halogen (QTH) unit for light-activating composite resins. Materials and Methods: Mesioocclusal and distoocclusal Class II cavity preparations were made in 72 sound extracted premolars. The buccolingual width was 2.5 mm and the gingival margins of all the cavities were placed 1.0 mm apical to the CEJ. The boxes were prepared 1.5 mm deep axially, making 144 slot cavities. Teeth were randomly divided into the following two groups (n = 72): (I) Universal Filtek Supreme XT; Universal Filtek Supreme XT + Flwable Filtek XT and Universal Filtek Supreme XT + Dyract Flow and (II) Filtek Z250; Filtek Z250 + Flwable Filtek XT and Filtek Z250 + Dyract Flow. Flowable materials were injected into the gingival floor of the cavity to a thickness of 1.0 mm. Each increment was cured for 20 s. One-half of the subgroups in each group were cured with QTH and the other half with LED light curing units (LCUs). After 1 week of incubation at 37°C, the specimens were thermocycled (5-55°C, x1500), immersed in 0.5% basic fuchsine dye for 24 h and sectioned and microleakage was evaluated at the gingival margin by two examiners using a 0-3 score scale. The data were analyzed using the Kruskal-Wallis and Mann-Whitney U tests. Results: The groups utilizing flowable liners had significantly less microleakage (P < 0.05). No significant difference was identified between Universal Filtek Supreme XT and Filtek Z250 composites with and without flowable materials. There was no significant between utilizing flowable composite or flowable compomer and between each similar subgroup when polymerized with either the LED or the QTH LCUs. Conclusions: A layer of flowable materials at the gingival floor of Class II composite restorations may be recommended to improve the marginal seal of a restoration.